Distribution of chemical forms of mercury in sediments from abandoned ponds created during former gold mining operations in Colombia (2020)
Total mercury (THg) and methylmercury (MeHg) were studied in sediments from 27 abandoned gold mining ponds (AGMPs) through small-scale artisanal gold mining in the district of San Juan in Chocó region of Colombia. The AGMPs were abandoned in the last century (1997) and were grouped into three distinct groups (2–6; 7–12; 13–20 years). Overall concentration (in ng g−1) pattern of THg in sediments varied from 39.06 to 1271.32 (avg. 209.57) with 174.81 (13–20 years), 205.56 (7–12 years) and 248.33 (2–6 years) respectively. MeHg concentrations accounted for 3.3–10.9% (avg. 6.5%) of THg and were significantly correlated with THg during all periods. Correlations between organic matter (OM) vs MeHg and THg were negative in the oldest pools, signifying a “dilution effect” or “natural burial” of THg and MeHg. Results for sequential extraction indicate that the fraction of elemental Hg (Hg-e) and organo chelated Hg (Hg-o) represent the main chemical forms of Hg in the sediments, regardless of the abandonment period, whereas the bioavailable fraction was only 0.12–1.65% of THg. The significant statistical relationship between MeHg, THg and OM suggests that these parameters control the distribution, mobility, toxicity and bioavailability of Hg in the sediments of these abandoned ponds. Evaluation of THg with sediment quality guidelines indicates that the values are on the higher side for Threshold effect concentration and Upper continental crust. Comparing of MeHg with many other regions outside Colombia is a worrying factor and needs immediate attention to protect the human health. © 2020 Elsevier Ltd